Clinical Study of Bell's Palsy at Tertiary Care: Our Experience - Bharathi, M. B.; Unisa, Thanzeem; Chandresh, Swathi; R., Venkatesh C.; S., Harsha (Annals of Otology and Neurotology, 2019)
Introduction Bell's palsy (BP) is the common cause of facial palsy. This study aims to report and analyze the age, sex distribution, symptomatology, site of lesion, and prognosis in 101 patients with (BP).Materials and Methods This is a cross-sectional study conducted at tertiary referral center, JSS Hospital, Mysuru. All patients consenting to participate in this study, of all ages, of either sex, both outpatients and inpatients with a diagnosis of BP during this study period were included.Results Of the 101 patients analyzed, maximum cases (25.7%) were in third decade of age; 55.4% were males, and both right and left sides of the face were equally involved. Maximum number of patients (50.5%) had a history of postaural pain at presentation Topodiagnostic tests showed majority of BP cases involving geniculate or suprageniculate regions (67.3%) in our study. 20.8% had lesion above the nerve to stapedius, and 11.9% had lesion below the nerve to stapedius. Electrodiagnostic test—electroneuromyography (ENMG)—was abnormal in 57 (67.1%) individuals at day 4. 50.4% of patients had a House-Brackmann (HB) facial nerve grade IV at presentation. 90% of the BP group in our study recovered normal to near-normal facial nerve function by the end of 28 days’ time.Conclusion Each case of BP should be evaluated with thorough clinical examination, topodiagnostic tests, and electrodiagnostic tests. Appropriate management will help in almost full recovery of disease.
Keywords: Bell's palsy; topodiagnostic tests; House-Brackmann facial nerve grading; electrodiagnostic test; electroneuromyography